Antimicrobial therapy during cancer treatment: Beyond antibacterial effects. (12th February 2021) - Ghanem, S.; Kim, C.J.; Dutta, D.; Salifu, M.; Lim, S.H.
Abstract: Cancer treatment options have evolved to include immunotherapy and targeted therapy, in addition to traditional chemoradiation. Chemoradiation places the patient at a higher risk of infection through a myelosuppressive effect. High clinical suspicion and early use of antimicrobials play a major role in decreasing any associated morbidity and mortality. This has led to a widespread use of antimicrobials in cancer patients. Antimicrobial use, however, does not come without its perils. Dysbiosis caused by antimicrobial use affects responses to chemotherapeutic agents and is prognostic in the development and severity of certain cancer treatment‐related complications such as graft‐versus‐host disease and Clostridioides difficile infections. Studies have also demonstrated that an intact gut microbiota is essential in the anticancer immune response. Antimicrobial use can therefore modulate responses and outcomes with immunotherapy targeting immune checkpoints. In this review, we highlight the perils associated with antimicrobial use during cancer therapy and the importance of a more judicious approach. We discuss the nature of the pathologic changes in the gut microbiota resulting from antimicrobial use. We explore the effect these changes have on responses and outcomes to different cancer treatment modalities including chemotherapy and immunotherapy, as well as potential adverse clinical consequences in the setting of stem cell transplant. Abstract :